The oral adverse effects of isotretinoin treatment in acne vulgaris patients: A prospective, caseucontrol study - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Background: Isotretinoin is the most effective therapy to treat severe acne vulgaris and its systemic adverse effects have been well documented, but little is known on dental side effects over the course of treatment. Objectives: This prospective case-control study aimed to evaluate the oral adverse effects of isotretinoin in Turkish patients with acne vulgaris; compare oral conditions between patients and normal controls; and investigate the association between salivary parameters and International Caries Detection and Assessment System (ICDAS) scores. Materials and Methods: For 6 months, the patients (n = 45) received isotretinoin daily (0.5 mg/kg). The age-matched untreated controls (n = 45) were patients without acne. Both groups were examined before the study and at 6 months for salivary flow, buffer capacity, microbiologic tests, and caries status (based on the ICDAS). Salivary parameters and ICDAS scores were analyzed by Spearman's rank correlations. Data were statistically analyzed by the MannuWhitney U test, Wilcoxon signed rank tests, and McNemar's Chi-square tests (P < 0.05). Results: Twenty-two isotretinoin-treated patients and 18 controls completed the study. At baseline, the groups were not significantly different in the evaluated parameters (P 0.05). At 6 months in the isotretinoin-treated group, salivary flow and buffer capacity significantly decreased, and the ICDAS scores significantly increased (P < 0.05). The changes in these criteria from baseline were insignificant in the controls (P > 0.05). Intraoral pathogen counts were not significantly different between the groups, compared to baseline (P > 0.05). Stimulated salivary parameters in both groups were not correlated significantly with the ICDAS scores. Conclusions: Isotretinoin significantly affected salivary flow, buffer capacity, caries lesion activity scores for 6 months. However, salivary parameters and caries lesion activity scores had no significant correlations.
Keywords: Acne vulgaris; dental caries; International Caries Detection and Assessment System; isotretinoin; salivary flow; SALIVA FLOW-RATE; BUFFERING CAPACITY; THERAPY; HEALTH; PH